2005
DOI: 10.1007/s10531-004-3918-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of dung and carrion beetles in a disturbed Mexican tropical montane cloud forest and on shade coffee plantations

Abstract: This paper analyzes the diversity of dung and carrion beetles (Scarabaeinae and Silphidae) in four human-induced habitats of a disturbed tropical montane cloud forest: polyspecific shade coffee plantations, monospecific shade coffee plantations, tropical montane cloud forest fragments, and clear cuts. The four habitats had similar richness, species composition, and assemblage structure of dung and carrion beetles. Differences were found in abundance and biomass levels for the four dominant species in the lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 24 publications
1
31
2
15
Order By: Relevance
“…Interestingly, the diversity of dung beetles in cacao plantations was similar to that of natural forest and much higher than the open areas (Table 2). Therefore, in contrast with other studies reporting a negative effect of forest conversion on the species richness of tropical dung beetles (Arellano et al 2005;Diaz et al 2010;Barragan et al 2011) this study showed that secondary forest and agroforestry systems may support a high portion of tropical dung beetles species, as has been suggested by Nichols et al (2007) and a previous study in Central Sulawesi . The high similarity of vegetation structure and microclimate between the cacao plantation and forest sites may explain both the capacity of the cacao plantation to maintain dung beetle diversity, and the significant differences between these communities and those of the open areas .…”
Section: Species Richness Across Land-use Types and Sampling Yearscontrasting
confidence: 98%
“…Interestingly, the diversity of dung beetles in cacao plantations was similar to that of natural forest and much higher than the open areas (Table 2). Therefore, in contrast with other studies reporting a negative effect of forest conversion on the species richness of tropical dung beetles (Arellano et al 2005;Diaz et al 2010;Barragan et al 2011) this study showed that secondary forest and agroforestry systems may support a high portion of tropical dung beetles species, as has been suggested by Nichols et al (2007) and a previous study in Central Sulawesi . The high similarity of vegetation structure and microclimate between the cacao plantation and forest sites may explain both the capacity of the cacao plantation to maintain dung beetle diversity, and the significant differences between these communities and those of the open areas .…”
Section: Species Richness Across Land-use Types and Sampling Yearscontrasting
confidence: 98%
“…Despite some of the apparent similarities in broad-scale assemblage responses to agroforestry and tree plantations, there have been fundamental differences in the responses according to region; in West Africa, beetle assemblages in cacao and palm plantations differed considerably from local forests and were dominated by savannah species (Davis and Philips 2005). However, in Mexico (Estrada et al 1998;Arellano et al 2005) and Costa Rica (Harvey et al 2006), the species occurring in agroforestry systems were subsets of the original forest fauna (only one open-habitat species, Canthon eurycelis, occurred in small numbers in cacao in Mexico [Estrada et al 1998], and one, Pseudocanthon perplexus, in banana in Costa Rica). Davis et al (2001) and Shahabuddin and Tscharntke (2005) in Indonesia and Bornea, respectively, found low dung beetle species richness in plantations compared to intact forest.…”
Section: The Conservation Value Of Shadementioning
confidence: 99%
“…Tropical dung beetles also play a role in protecting seeds from seed predators and in secondary seed dispersal (Andresen 2003). Studies of Neotropical dung beetles suggest that coffee and shade-tree crops can maintain species that avoid open habitats (Estrada et al 1998;Arellano et al 2005;Harvey et al 2006). Fewer studies have examined the value of regenerated forest patches in maintaining dung beetle diversity (Medina et al 2002;Horgan 2007) and I am unaware of any study that has determined the response of tropical dung beetles over small temporal scales (i.e., B1 year) to changes in vegetation structure on established farms in any tropical montane region.…”
Section: Introductionmentioning
confidence: 99%
“…Most prior studies of beetle faunas in coffee have examined total abundance patterns from foliage-collected beetles (Philpott, Greenberg, Bichier, & Perfecto, 2004), have sampled from a few shade trees (Perfecto, Hansen, Vandermeer, & CartıŽn, 1997), or have included only dung and/or carrion beetles (e.g. Arellano, Favila, & Huerta, 2005;Pineda, Moreno, Escobar, & Halffter, 2005). Using beetle morphospecies analysis with pyrethrum knockdown samples from coffee plants in western Ecuador, Richter, Klein, Tscharntke, and Tylianakis (2007) found high beetle species richness near coffee plantation edges, but no difference between traditionally managed, and abandoned coffee plantations.…”
Section: Introductionmentioning
confidence: 99%